EFEKTIVITAS PENGGUNAAN MEDIA TANAM AGRONIKA PADA PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS (Zea mays saccharata sturt) - dewantara Rio; Refki Sanjaya (Universitas Muhammadiyah Kotabumi, 2023)
Abstract : Sweet corn production at the Indonesian farmer level is still very low. The low production is due to the many obstacles faced in the cultivation of sweet corn, including low soil fertility. The tendency of farmers to currently use inorganic fertilizers. The negative effect of using inorganic fertilizers is that the physical condition of the soil becomes worse, crop yields decrease from previous results. An alternative to overcome this negative effect is by using organic fertilizers. This fertilizer tends to increase the amount of water that can be held in the soil. in the soil and available to plants, as well as a source of energy for micro-organisms. The aim is to determine the effectiveness of the use of agronomic fertilizers on the growth of sweet corn, and to determine the level of effectiveness of the use of agronic fertilizers. This study consisted of using agronic fertilizers with different dosage levels. The observed plant growth parameters were plant height, number of leaves, and stem diameter, while the observed production parameters were stover weight, firm weight and non-husked weight. Data analysis. Parameter data obtained were analyzed statistically with 95% variance then continued with Duncan's test at 5% level. The results of the application of agronomic fertilizer types and dose levels of 2.4 Kg per plot, 4.8 Kg per plot, 7.2 Kg per plot, on sweet corn plants showed the highest growth and production with a better dose level of 7.2 per plot. Keywords: Dosage, Sweet Corn, Growth, Organic Fertilizer, Productio